Risk Factor Evaluation of Non Alcoholic Fatty Liver Disease in Lean Individual - Mohsin, Mostafa Noor; Ali Haider, Salahuddin Mohammed; Akter, Farhana; Ahmed, Ershad Uddin; Paul, Binoy (Journal of Chittagong Medical College Teachers' Association, 2022)
Background : Non-Alcoholic Fatty Liver Disease (NAFLD) is epidemic around the world. Bangladesh is also experiencing an increasing trend of NAFLD. Obesity is a common clinical phenotype associated with NAFLD, which is linked to metabolic syndrome and related comorbidities, including type II diabetes, hypertension and dyslipidemia. Clearly, not all obese subjects develop NAFLD and NAFLD also can be found in non-obese patients. This subset of individuals, known to have ‘lean NAFLD’ or ‘non-obese NAFLD’, is growing increasingly prevalent. NAFLD in lean patients appears to be more common among Asians. So it is important to look for risk factors for NAFLD in lean patients for prevention of advanced liver disease. The objective of our study was to find out the risk factors of NAFLD in lean (Nonobese) individual. Materials and methods: It was prospective observational study done on 100 patients attending in the Gastroenterology Department and OPD of Chittagong Medical College Hospital after approval of Ethical and Review Committee of CMC and grant from DGHS. Total 100 patients having 18 to 65 years of age, were taken as study subjects who met inclusion criteria. Informed written consent was obtained from the patients or attendant after full explanation of the purpose of the study. Fasting Blood Glucose (FBS) Fasting lipid profile, SGPT, SGOT, Ultrasonography of hepatobiliary system and Fibrosan were done. All necessary data was included in the data collection sheet and was analyzed by Microsoft excel and SPSS-23. Results: 100 patients were included in this study. Mean age of this study with age was in between 18 years to 65 years.Male to female ratio was 3:1 in the studied population.The majority of the lean patient with NAFLD (31%) was in the age group 40-49 years. The majority of the lean patient with NAFLD (83%) was in normal BMI range 18.5-22.99 kg/m2 and 13% had BMI <18.50 kg/m. Out of 100patients diabetes and hypertension were found 22% and 17% of patients respectively. 22% and 17% patients. 65% and 37% patients had raised SGPT and SGOT respectively. Out of 100 subjects, 50% had raised triglyceride level (50%) and 18% had raised LDL cholesterol (18%) level.According to Ultrasonography findings 68% were in Grade I, 11% in Grade II and only 1 patient was in Grade III fatty liver. Fibroscan of 100 subjects, Significant fibrosis ( ³2 F) was observed in 9%, while advanced fibrosis (F4) was seen in 4% of patients. As per steatosis score 36% was in S2 and 34% were in S3 grade. Median fibrosis score and steatosis score was significantly higher in patients with high SGPT compared to patients with normal SGPT (p <0.005) whereas median fibrosis score and steatosis score was higher in patients with high SGOT compared to patients with normal SGOT, but only the difference in steatosis score reached statistical significance (p<.042). AUC of SGPT for discriminating fibrosis grade F0-F1 from Grade F2-F4 was 0.565 (95% CI: 0.404-0.726, p=0.519). AUC of SGOT for discriminating fibrosis grade F0-F1 from Grade F2-F4 was 0.573 (95% CI: 0.342-0.803, p=0.474). This indicated that there was no significant role of SGPT or SGOT values for prediction of significant fibrosis ( ³2F).AUC of SGPT for discriminating steatosis grade S0-S2 from Grade S3-S4 was 0.565 (95% CI: 0.404-0.726; p=0.519). AUC of SGOT for discriminating steatosis grade S0-S2 from Grade S3-S4 was 0.573 (95% CI: 0.342-0.803, p=0.474). This indicated that both SGPT and SGOT had significant role for prediction of significant steatosis ( ³3S).Higher age (p <0.028) and female sex (p<0.013) were revealed as independent predictive factors for significant fibrosis ( ³F2) in non-obese NAFLD patients on performing multivariate binary logistic regression. Conclusion Lean NAFLD is now frequently recognized in day-to-day clinical practice, however, the data on epidemiology, risk factors, physiopathology, distinctive histologic changes, natural history and treatment of this entity are still scanty. From a biological point of view, lean NAFLD be haves much like obese NAFLD. Our study may help to find out risk factors in nonobese NAFLD which may help prevention of advance liver disease by early intervention. JCMCTA 2022 ; 33 (1) : 56-65